Digital games & special education - Chaidi , Irene; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Educators define three factors of interaction or as they refer to the 3 C's in education: Children (children), Community (communication), and Computer (computers) [1]. Information and Communication Technologies are an integral tool of the educational process for modern educational systems, helping the learning process to turn from passive to active, pushing each student to learn independence and autonomy. In recent years, the sciences of education have turned their attention and have already recognized the importance of games and even digital games as a learning tool, emphasizing the benefits for students with or without educational needs.